Islam, secularism and danger: a reconsideration of the link between religiosity, radicalism and rebellion in Central Asia. Issue 3 (2nd July 2016) - Montgomery, David W.; Heathershaw, John
ABSTRACT: In equating political Islam with radicalism and rebellion against the state, security analysts make a number of assumptions about the religious, the secular and security. Within the Central Asian context, the discursive fusing of religiosity with radicalism produces a bogeyman in which national and foreign governments, although offering quite different countermeasures, have found a common enemy. This securitisation of Islam distorts our understanding of these movements whose approach is seldom 'radical' in form. We identify six claims which are axiomatic to both international and national secularist security discourses with respect to Islam in the region. We then demonstrate that popular Muslim discourse and political practice – in the findings of an original survey and ethnographic research in Kyrgyzstan and Tajikistan – provide a more complex picture than that found in elite discourses. While the six propositions can be refuted in objective terms, they remain relevant to how the problem is subjectively produced and reproduced in elite discourse and practice. As particular secularist claims about Islam, they inform national and international policies towards religious freedom and Islamic movements across Central Asia. Many of these themes appear in weaker and ambiguous forms in popular discourse and continue to limit Muslim political participation.